CD200 in asthma. (July 2019) - Lauzon-Joset, Jean-François; Marsolais, David; Tardif-Pellerin, Éliane; Patoine, Dany; Bissonnette, Elyse Y.
Highlights: CD200 and CD200R1 expression is elevated in the lung, including on epithelial cells and macrophages. Asthma pathogenesis is associated with a dysregulation of CD200. CD200R1 activation in animal models of asthma is able to inhibit the cardinal features of asthma pathogenesis. The role of soluble CD200 in immunology is still unclear with reports of both anti- and pro-inflammatory functions. Abstract: Constant exposure to foreign particles in the airways requires tight immune regulation in order to maintain sufficient anti-microbial defences, while preventing immunopathological responses that could impair gas exchange. Dysregulation of immunoregulatory pathways has been associated with asthma and allergy. This review will focus on the CD200 regulatory pathway and its role in the asthmatic cascade. CD200 and its receptors are highly expressed in the lung, on epithelial cells and leukocytes, and emerging evidence links dysregulation of the CD200 pathway with asthma. Moreover, pharmacological modulation of CD200 receptors was shown to improve clinical and inflammatory outcomes of preclinical asthma models. Therefore, the involvement of CD200 in asthma is increasingly recognized and preclinical studies support the contention that it could constitute an additional target to alleviate asthma exacerbation and/or reduce disease severity.